2022
DOI: 10.1590/fst.101321
|View full text |Cite
|
Sign up to set email alerts
|

Non-dairy plant-based milk products as alternatives to conventional dairy products for delivering probiotics

Abstract: Dairy products are important to the human diet and are one of the four essential food groups. Conventional fermented cow milk products possessed a variation of bioactive components that enhance the human body's physiological processes. However, traditional milk products can be replaced by non-dairy plant-based milk which is produced mainly from fruits and seeds such as soy, coconut, almond, rice, peanut, lupin, cashew, and hemp. Fermented plant-based milk is the outcome of intense bacterial activity of the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 74 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…One study indicated that the global coconut milk market was estimated to be USD 814.4 million in 2020 and that it would grow at a 9.3% compound annual growth rate to reach USD 1775.4 million by 2027 [ 2 ]. Another study showed [ 3 ] that coconut milk was a good substitute for cow milk. On the one hand, cow milk contains a large amount of lactose, which has the highest allergenic potential, while coconut does not contain lactose [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…One study indicated that the global coconut milk market was estimated to be USD 814.4 million in 2020 and that it would grow at a 9.3% compound annual growth rate to reach USD 1775.4 million by 2027 [ 2 ]. Another study showed [ 3 ] that coconut milk was a good substitute for cow milk. On the one hand, cow milk contains a large amount of lactose, which has the highest allergenic potential, while coconut does not contain lactose [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed [ 3 ] that coconut milk was a good substitute for cow milk. On the one hand, cow milk contains a large amount of lactose, which has the highest allergenic potential, while coconut does not contain lactose [ 3 ]. On the other hand, the fat content of cow milk is 3.27 g/100 mL, and for coconut milk it is 5.04 g/100 mL [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, another aspect of ingested probiotic food pathway and viability may be investigated. The texture and nutrient density and the complexity of the food matrix are responsible for releasing the nutrients delivering specific metabolites and strains to the intestines [104,105]. Moreover, the density and variety of live cultures may be the essential indicators for increasing the variety of gut microbiome [77].…”
Section: Plant-based Drinks From Grains and Fermented Drinks Productionmentioning
confidence: 99%